COMparison of Platelet reactivity following prAsugrel and ticagrelor loading dose in ST-Segment elevation myocardial infarctION patients: The COMPASSION study. (September 2015) - Laine, Marc; Gaubert, Mélanie; Frère, Corinne; Peyrol, Michael; Thuny, Franck; Yvorra, Serge; Chelini, Virginie; Bultez, Bruno; Luigi, Stephane; Mokrani, Zair; Bessereau, Jacques; Toesca, Richard; et al.
Abstract Prasugrel and ticagrelor are potent P2Y12-ADP receptor antagonists which are superior to clopidogrel in acute coronary syndromes. To date no clinical trial directly compared these two drugs. Platelet reactivity correlates with ischemic and bleeding events in patients undergoing percutaneous coronary intervention. Recent pharmacological studies have observed a delayed onset of action of these two drugs in ST-segment elevation myocardial infarction (STEMI). We provide the first adequately powered pharmacological study comparing PR following ticagrelor and prasugrel loading dose (LD) in STEMI patients when the maximal biological effect is reached. In the present study, ticagrelor was associated with a lower rate of high on-treatment PR compared to prasugrel.